Biomedical Application of Nanogels: From Cancer to Wound Healing - Mohammad Zafaryab; Komal Vig (Molecules)
Nanogels are polymer-based, crosslinked hydrogel particles on the nanometer scale. Nanogels developed from synthetic and natural polymers have gathered a great deal of attention in industry and scientific society due to having an increased surface area, softness, flexibility, absorption, and drug loading ability, as well as their mimicking the environment of a tissue. Nanogels having biocompatibility, nontoxic and biodegradable properties with exceptional design, fabrication, and coating facilities may be used for a variety of different biomedical applications, such as drug delivery and therapy, tissue engineering, and bioimaging. Nanogels fabricated by chemical crosslinking and physical self-assembly displayed the ability to encapsulate therapeutics, including hydrophobic, hydrophilic, and small molecules, proteins, peptides, RNA and DNA sequences, and even ultrasmall nanoparticles within their three-dimensional polymer networks. One of the many drug delivery methods being investigated as a practical option for targeted delivery of drugs for cancer treatment is nanogels. The delivery of DNA and anticancer drugs like doxorubicin, epirubicin, and paclitaxel has been eased by polymeric nanogels. Stimuli-responsive PEGylated nanogels have been reported as smart nanomedicines for cancer diagnostics and therapy. Another promising biomedical application of nanogels is wound healing. Wounds are injuries to living tissue caused by a cut, blow, or other impact. There are numerous nanogels having different polymer compositions that have been reported to enhance the wound healing process, such as hyaluronan, poly-L-lysine, and berberine. When antimicrobial resistance is present, wound healing becomes a complicated process. Researchers are looking for novel alternative approaches, as foreign microorganisms in wounds are becoming resistant to antibiotics. Silver nanogels have been reported as a popular antimicrobial choice, as silver has been used as an antimicrobial throughout a prolonged period. Lignin-incorporated nanogels and lidocaine nanogels have also been reported as an antioxidant wound-dressing material that can aid in wound healing. In this review, we will summarize recent progress in biomedical applications for various nanogels, with a prime focus on cancer and wound healing.